An integrated comparative physiology and molecular approach pinpoints mediators of breath-hold capacity in dolphins. Issue 1 (28th October 2021) - Blawas, Ashley M; Ware, Kathryn E; Schmaltz, Emma; Zheng, Larry; Spruance, Jacob; Allen, Austin S; West, Nicole; Devos, Nicolas; Corcoran, David L; Nowacek, Douglas P; Eward, William C; Fahlman, Andreas; et al.
Abstract: Background and objectives: Ischemic events, such as ischemic heart disease and stroke, are the number one cause of death globally. Ischemia prevents blood, carrying essential nutrients and oxygen, from reaching tissues, leading to cell and tissue death, and eventual organ failure. While humans are relatively intolerant to ischemic events, other species, such as marine mammals, have evolved a unique tolerance to chronic ischemia/reperfusion during apneic diving. To identify possible molecular features of an increased tolerance for apnea, we examined changes in gene expression in breath-holding dolphins. Methodology: Here, we capitalized on the adaptations possesed by bottlenose dolphins ( Tursiops truncatus ) for diving as a comparative model of ischemic stress and hypoxia tolerance to identify molecular features associated with breath holding. Given that signals in the blood may influence physiological changes during diving, we used RNA-Seq and enzyme assays to examine time-dependent changes in gene expression in the blood of breath-holding dolphins. Results: We observed time-dependent upregulation of the arachidonate 5-lipoxygenase (ALOX5) gene and increased lipoxygenase activity during breath holding. ALOX5 has been shown to be activated during hypoxia in rodent models, and its metabolites, leukotrienes, induce vasoconstriction. Conclusions and implications: The upregulation of ALOX5 mRNA occurred within the calculated aerobic dive limit of the species, suggesting that ALOX5 may play a role in the dolphin's physiological response to diving, particularly in a pro-inflammatory response to ischemia and in promoting vasoconstriction. These observations pinpoint a potential molecular mechanism by which dolphins, and perhaps other marine mammals, respond to the prolonged breath holds associated with diving. Lay Summary: Reductions in blood flow are associated with tissue damage in humans; however, marine mammals have evolved remarkable tolerance to reductions in tissue blood flow during diving. We found that changes in gene expression in breath-holding dolphins may support a response to diving highlighting a potential molecular underpinning for apnea tolerance.